Basal fertilizer effects on weed occurrence and rice yield in acid upland soil of West Africa at Bénin - Koné, B.; Traoré, K.; Touré, A. (Science Publishing Group, 2014)
Fertilizers application is required in order to improve rice production in low fertile soils of West Africa. This practice can also increase weed pressure in rice field, thereby reducing yield significantly. Chemotropism of weed was hypothesized to identify nutrient effects on weed abundance and biomass production as well as rice yield for suitable recommendation of basal fertilizer in terre de barre soil agro-ecology. Two years (2005 and 2006) fertilizer omission trial including nitrogen (N), potassium (K), phosphorus (P), calcium (Ca), magnesium (Mg) and zinc (Zn) was conducted in a randomized completed block design, with 4 replications at the Africa Rice Center experiment station, in Benin. The New Rice for Africa named NERICA 4 was sown. Weed dominance-abundance indices and biomass, as well as, rice grain yield were assessed. Results show that Digitaria horizontalis Wild and Mariscus cylindristachyus Steudel were the most dominant weed species in rainfed rice fields on terre de barre soils and the omission of Zn has ability to discriminate among weeds. Base on weed biomass (60.11 – 129.26 g m-2) reduction by 36 – 53% in treatments with Ca, Mg and P omission, the application of N, K and Zn was recommendable for basal fertilizer as integrated weed management practice for boosting rice production on terre de barre soils in West Africa.